Gender differences in the labor market effects of the dollar - Linda Goldberg; Joseph Tracy (Federal Reserve Bank of New York, 2001)
Although the dollar has been shown to influence the expected wages of workers, the analysis to date has focused on the male workforce. We show that exchange rate fluctuations also have important implications for women's wages. The dominant wage effects for women—like those for men—arise at times of job transition. Changes in the value of the dollar can cause the wage gap between women who change jobs and women who stay on in their jobs to expand or contract sharply, with the most pronounced effects occurring among the least educated women and women in highly competitive manufacturing industries. In addition, it appears that women who stay on in their jobs show greater wage sensitivity to currency movements than do their male counterparts.
Keywords: F31; F3; F4; J30; E24; 330; Wages; Labor market; Dollar; American; Foreign exchange; Wechselkursrisiko; Fraueneinkommen; USA